Seasonal variation of oceanographic processes in Indus river estuary - KALHORO, NOOR AHMED; HE, ZHIGUO; XU, DONGFENG; INAM, ASIF; MUHAMMAD, FAIZ; SOHOO, NAIMATULLAH (MAUSAM, 2017)
Field investigations were conducted to study spatial and temporal (seasonal) variations in meteorological, hydrodynamic and hydrological variables in Indus River Estuary. The investigations were undertaken during wet, (moderate fluvial discharge), flood (highest fluvial discharge) and dry (zero fluvial discharge) seasons to obtain surface and near bed data during flood and ebb tides. Tides were semidiurnal, showing an asymmetric pattern with longer ebb tides and shorter flood tides. The hydrodynamic data revealed strong seasonal variation, the ebb velocities were significantly higher than flood current velocities during wet season, whereas a slight difference was found in current velocities during dry season, while the ebb phase lasted longer than flood during wet season; however no significant difference was observed during dry season. On the other hand during flood period the water currents were substantially higher and unidirectional related to the strong river flow. Turbidity values were considerably higher during flood season, than wet and dry seasons along the channel. However hydrological parameters such as temperature and dissolved Oxygen also revealed seasonal and spatial fluctuations, though they were within permissible range. The salinity distribution along the channel was related to the incoming river flow and tidal propagation. Higher salinity values were recorded in dry season, suggested that salinity variation at Estuary was due to salt intrusion from the North Arabian Sea, related to the absent of fluvial discharge form Indus River. Present study revealed substantial changes for hydrology and hydrodynamic conditions of the Indus River Estuary, related to the varying Indus River flow, as well as winds are another important atmospheric force in this region which enhanced the tidal forcing during southwest monsoon.